The First World War and the refugee crisis: historiography and memory in the Greek context - Salvanou, Emilia (Historein, 2017)
The paper aims to trace the historiographical construction of the Great War in the Greek national narrative. Its main argument is that although the First World War was more or less a shared experience among its participants, the way it was constructed as an event is aligned not to the experience as such, but to the national discourse that subsequently prevailed. In the Greek case, its historiographical construction took place in three main stages: the first during the interwar period, when the temporal framework of the event were set (the war decade of 1912–1922) and the interest was mainly in the military and political aspects. The second stage developed after the Second World War, when there was a turn towards testimonies and the field of refugee studies was shaped. It was during this stage that the memory of the refugees found its place in the national narrative. The third stage began in the last quarter of the twentieth century, when a split developed in the way the event is constructed in public and lay history and in the way it is constructed in academic historiography, where the limits of national historiographies are critiqued.